The assembly processes and network characteristics of bacterial, fungal and archaeal communities in the middle Yangtze River and river-connected lakes - Wang, Fenglin; Li, Si; Li, Pinjian; Feng, Chuanzhe; Zhao, Zhijie; Yang, Yulong; Han, Fulei; Xue, An; Li, Zhenshan; Han, Peng (Frontiers in Microbiology, 2025)
Despite the crucial ecological roles of bacterial, fungal and archaeal communities in rivers and lakes, their interactions and dynamic changes in large, hydrologically-connected river–lake systems remain poorly understood. This study investigated the biogeographic patterns, assembly processes and co-occurrence network characteristics of bacterial, fungal and archaeal communities in the middle reaches of Yangtze River (MYR) and its two largest connected lakes, Dongting Lake (DTL) and Poyang Lake (PYL). Our results revealed significant spatial heterogeneity in microbial diversity and composition, with higher sedimentary microbial diversity in lakes than in the river. Stochastic processes, particularly dispersal limitation, dominated community assembly across all habitats. β-NRI analysis showed that deterministic processes were more influential for planktonic bacterial and archaeal communities in the lakes. Co-occurrence network analysis demonstrated that inter-domain cooperation was prevalent in PYL, whereas intra-domain interactions were more common in MYR and DTL, reflecting distinct hydrological connectivity. Keystone taxa differed between rivers and lakes, with rare taxa prevailing in MYR and both rare and abundant taxa contributing in lakes. Our findings highlight how connectivity and flow dynamics fundamentally shape microbial ecology, providing insights into for the management and conservation of large river–lake ecosystems.